A Polyphenol‐Rich Diet Increases the Gut Microbiota Metabolite Indole 3‐Propionic Acid in Older Adults with Preserved Kidney Function. Issue 21 (6th April 2022) - Peron, Gregorio; Meroño, Tomás; Gargari, Giorgio; Hidalgo‐Liberona, Nicole; Miñarro, Antonio; Lozano, Esteban Vegas; Castellano‐Escuder, Pol; González‐Domínguez, Raúl; del Bo', Cristian; Bernardi, Stefano; Kroon, Paul A.; Cherubini, Antonio; et al.
Abstract : Scope: Dietary polyphenols can alter the gut microbiota (GM) and promote the production of bioactive metabolites. Several indoles result of GM metabolism of dietary tryptophan have been associated with intestinal barrier integrity. Our aim is to study the changes in GM‐derived indoles during a polyphenol‐rich (PR) diet intervention in older adults. Methods and Results: Randomized, controlled, crossover trial in adults ≥ 60 years living in a residential care facility during an 8‐week PR versus control diet ( n = 51). Seven GM‐tryptophan metabolites are measured in serum, and metataxonomic analysis of GM is performed on fecal samples. Exploratory subgroup analyses are performed based on renal function (RF). The PR‐diet significantly increases serum indole 3‐propionic acid (IPA) in subjects with normal RF, but not in subjects with impaired RF. Other GM‐tryptophan metabolites are not affected. Comparison of baseline GM composition shows shifts in Bacteroidales order members as well as higher abundance of Clostridiales in participants with normal RF. During the trial, variations of IPA are associated with changes in C‐reactive protein (β = 0.32, p = 0.010) and GM, particularly with the Clostridiales ( r = 0.35, p < 0.001) and Enterobacteriales ( r = −0.15, p < 0.05) orders. Conclusion: A PR diet increases the serum concentration of IPA in older adults with normal RF. Our findings may be important when defining appropriate dietary interventions for older adults. Trial registration number : ISRCTN10214981 (https://doi.org/10.1186/ISRCTN10214981 ). Abstract : In a randomized, controlled, crossover trial involving 51 adults ≥ 60 y receiving a PR‐diet for 8 weeks we observed that the PR‐diet significantly increased serum indole 3‐propionic acid (IPA), and the effect was dependent on renal function. During the trial, variation of IPA in volunteers with normal renal function was associated with changes in C‐reactive protein and gut microbiota, particularly with the Clostridiales and Enterobacteriales orders.